2019
DOI: 10.1155/2019/8047191
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical Water Extraction of Antioxidants from Curculigo latifolia Root

Abstract: This study aims to extract antioxidant compounds from Curculigo latifolia root by subcritical water extraction (SWE). The influence of extraction temperature and time on the antioxidant activity of C. latifolia root extract was investigated in terms of extraction yield, total phenolic content (TPC), total flavonoid content (TFC), 2, 2′-azino-bis-3-ethylbenzothiazoline-6-sulphonic acid (ABTS), and 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical. The highest extraction yield (36.5%), TPC (92.55 mg GAE/g), TFC (13.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…The presence of H-bonds is definitely attributed to form a major interaction and regarded to be the main driving force of conformational change of the receptor upon ligand binding. To the best of our knowledge, our present studies were found to be as the first studies that revealed the molecular docking with the compounds that present in C. latifolia extracts and this works is based on continuation from our previous studies that involving with antioxidant activity and screening of compounds by LC-MS analysis 16 . Thus, these studies have been pointed out the potential of phlorizin by inhibiting the activity of α-glucosidase and DPP (IV) enzyme as the new alternative for antidiabetic drugs that potentially being used in the treatment for type 2 diabetes.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The presence of H-bonds is definitely attributed to form a major interaction and regarded to be the main driving force of conformational change of the receptor upon ligand binding. To the best of our knowledge, our present studies were found to be as the first studies that revealed the molecular docking with the compounds that present in C. latifolia extracts and this works is based on continuation from our previous studies that involving with antioxidant activity and screening of compounds by LC-MS analysis 16 . Thus, these studies have been pointed out the potential of phlorizin by inhibiting the activity of α-glucosidase and DPP (IV) enzyme as the new alternative for antidiabetic drugs that potentially being used in the treatment for type 2 diabetes.…”
Section: Discussionmentioning
confidence: 74%
“…The total volume of the high-pressure stainless steel vessel was 50 ml, thus, it was filled with about 2 g of the C. latifolia root and fruit extract respectively. Similar to what was done in our previous research work, the independent variables were measured at optimum conditions which were set at 180 °C for 30 min of extraction time 16 . All other parameters were held constant, comprising of an extraction pressure of 100 bar, the flow rate of 0.5 ml/min, and water to the solvent ratio of 1:10 w/v .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…possess some biological activities, such as cycloartane glycosides, which are used for leukemia treatment. Curculigosides F was found to inhibit hepatitis B virus (HBV) and antigen (HBeAg) in the HepG2.2.15 cell line, while chlorophenolic glycoside groups, such as curculigine M, curculigine N, and curculigine O, were reported to induce the proliferation of osteoblasts, orcinol glycosides, and 5,7,4′-trihydroxy-3′-methoxy flavone, which have antioxidant activity [ 4 , 5 , 6 ]. The phenolic group of Curculigo spp.…”
Section: Introductionmentioning
confidence: 99%
“…For C. latifolia , the extract of the tuber displayed higher antioxidant activity than that of a leaf in a DPPH scavenging assay and a superoxide dismutase assay [ 70 ]. The subcritical water extraction of C. latifolia roots displayed significant antioxidant activity in DPPH and ABTS assays, and further LC-MS analysis revealed that phenolic compounds such as monobenzone, hydroquinone, phloridzin, pomiferin, mundulone, scandenin, and dimethyl caffeic acid were the main active compounds [ 71 ].…”
Section: Pharmacological Propertiesmentioning
confidence: 99%